Lexicography and Neology: Building Bridges through a Multilingual Approach with ENEOLI - Tallarico, Giovanni; Costa, Rute; Salgado, Ana; Freixa, Judit; Heylen, Kris; Humbley, John; Kernerman, Ilan; Klosa-Kückelhaus, Annette; Ostroški Anić, Ana; Vezzani, Federica; Balnat, Vincent; Božović, Petar; et al. (Lexikos, 2025)
Neology, the study of new word formations and new word meanings, remains an underrepresented yet critical dimension of linguistic research. This paper explores the efforts of the European Network on Lexical Innovation (ENEOLI) COST Action, launched in October 2023, in addressing key gaps in the study of lexical innovation in connection with lexicography. With 343 participants from 51 countries as of March 2025, ENEOLI seeks to build a comprehensive, multilingual approach to neology research. This initiative focuses on developing digital resources, comparative studies, and professional training to elevate the understanding of neology within the linguistic community, including the development of a multilingual glossary of the meta-terminology of neology. By integrating lexicographic and computational methodologies, ENEOLI sets a benchmark for multilingual research. This initiative not only contributes to a deeper understanding of neology but also provides resources that support its application across diverse academic and professional contexts, including translation, education, and digital humanities. Through its collaborative framework, ENEOLI highlights the significance of lexical innovation in understanding language evolution and its cultural and social dimensions.Keywords: ENEOLI, neology, lexicography, lexical innovation, language change, multilingual glossary, terminology